(untitled) (Global Journal of Science Frontier Research, 2017)
New Cartesian physics based on the identity of space and matter and makes the principle of uncertainty Heisenberg by a principle of physical irrationality of points of space-matter from which naturally follows a probabilistic way of describing the developments in quantum mechanics. New Cartesian physics relates the probability of an event in quantum mechanics with the factor of Lorentz of the special theory of relativity, which turns idle geometric space in the physical, in which space moves.